"Costruzione del viadotto": MA‐XRF in the pictorial executive technique of Agostino Bosia. (24th April 2020) - Nervo, Marco; Romano, Francesco P.; Caliri, Claudia; Piccirillo, Anna; Triolo, Paolo; Demonte, Daniele; Gatti, Alessandro; Vergallo, Eleonora; Cardinali, Michela; Ferrero, Marianna
Abstract : During the restoration process of a huge oil canvas (266 cm × 361 cm × 3 cm) by Agostino Bosia, a deep diagnostic campaign was carried out to characterize the original materials and those stratified over time. The activity was supported by the technologies available today in the field of conservation of the Cultural Heritage. Multispectral analyses (UV fluorescence, infrared reflectography, infrared false‐colour post‐production, digital radiography) associated with punctual (X‐Ray Fluorescence, Fibre Optics Reflectance Spectroscopy) and microstratigraphic analyses (visible light and UV fluorescence optical microscopy and SEM–EDX) allowed to accurately reconstruct the artist's creative process and to identify the pictorial materials. The well‐known analytical protocol was finally combined with Macro X‐ray Fluorescence scanning technique (MA‐XRF) in order to consolidate the results of the punctual, non‐invasive analyses over a large area of the canvas.